Continuance intention in gamified mobile applications: A study of behavioral inhibition and activation systems - Aydınlıyurt, Elif Tuğba; Taşkın, Nazım; Scahill, Shane; Toker, Ayşegül (International journal of information management, 2021)
This study seeks to investigate the effects of Behavioral Activation System (BAS), known as approach motivation, and Behavioral Inhibition System (BIS), known as avoidance motivation, that are expected to influence individuals’ post-adoption behaviors in gamified mobile applications. A survey-based research methodology was used, and the impacts of BAS and BIS on Information Systems Continuance are examined. The results show that reward responsiveness has the most significant effect on user satisfaction and continuance intention. Fun-seeking plays an essential role in continuance intention; however, it does not significantly affect satisfaction, as drive does not affect either satisfaction or continuance intention. BIS has a significant and negative effect on individual satisfaction, but no effects were found related to continuance intention. The findings of this study improve the understanding of the differences between these motivations related to Information Systems Continuance. Significant practical implications that gamified mobile application developers can adopt are proposed. •Reward responsiveness has the biggest effect on user satisfaction and IS continuance.•Fun-seeking positively affects IS continuance.•Drive has no significant effect on both satisfaction and IS continuance.•BIS has a negative influence on satisfaction.•Fun-seeking has no effect on satisfaction, as BIS on continuance intention.